2021
DOI: 10.1136/bmjresp-2020-000848
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the STOP-Bang questionnaire as a screening tool for obstructive sleep apnoea in patients with cardiovascular risk factors: a systematic review and meta-analysis

Abstract: IntroductionObstructive sleep apnoea (OSA) is highly prevalent in patients with cardiovascular risk factors and is associated with increased morbidity and mortality. This review presents the predictive parameters of the STOP-Bang questionnaire as a screening tool for OSA in this population.MethodsA search of databases was performed. The inclusion criteria were: (1) use of the STOP-Bang questionnaire to screen for OSA in adults (>18 years) with cardiovascular risk factors; (2) polysomnography or home sleep a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 65 publications
(84 reference statements)
1
22
2
Order By: Relevance
“…We compared 10-year cardiovascular risk in patients with T2DM according to the STOP-Bang score. Similar to our study, other studies have shown that the STOP-Bang score can be used to identify patients at risk of developing fatal or nonfatal CHD as well as fatal or nonfatal stroke [ 17 , 18 , 35 ]. In a recent prospective study that enrolled 435 patients, it was demonstrated that a STOP-Bang score ≥5 was associated with increased all-cause mortality and cardiovascular mortality over 36 months follow-up (95 patients died, 34 of them due to cardiovascular events), with a hazard ratio of 3.12 [ 18 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We compared 10-year cardiovascular risk in patients with T2DM according to the STOP-Bang score. Similar to our study, other studies have shown that the STOP-Bang score can be used to identify patients at risk of developing fatal or nonfatal CHD as well as fatal or nonfatal stroke [ 17 , 18 , 35 ]. In a recent prospective study that enrolled 435 patients, it was demonstrated that a STOP-Bang score ≥5 was associated with increased all-cause mortality and cardiovascular mortality over 36 months follow-up (95 patients died, 34 of them due to cardiovascular events), with a hazard ratio of 3.12 [ 18 ].…”
Section: Discussionsupporting
confidence: 83%
“…In a study from 2008, Chung et al [ 47 ] proved that STOP-Bang score has a sensitivity of 100% for AHI ≥ 30; however, the small specificity of 37.0% means that there are also many false positive cases reported, suggesting that even though the STOP-Bang questionnaire is a very quick and easy tool to apply for the screening of OSA, in order to properly diagnose and treat this category of patients they should be referred for polysomnography or home sleep apnea testing (HSAT), as is recommended by the American Academy of Sleep Medicine (AASM) [ 48 ]. However, many patients unfortunately refuse undergoing such expensive investigations, and in these conditions, undiagnosed cases can significantly increase the burden on the public health system and also decrease the quality of life of patients, thus necessitating the acceptance of a screening method with high sensitivity, even at the cost of low specificity, such as the STOP-Bang questionnaire [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that the SBQ could be an effective tool for screening OSA (AHI ≥ 5) in patients with cardiovascular risk factors [20]. Although the SBQ has been validated in different populations, there may still be potential biases in some validation studies due to the possible self-selection bias of patients themselves [11].…”
mentioning
confidence: 99%